2018
DOI: 10.18069/firatsbed.387808
|View full text |Cite
|
Sign up to set email alerts
|

Ci̇nsi̇yeti̇n Tekno-Pedagoji̇k Alan Bi̇lgi̇si̇ Üzeri̇ndeki̇ Etki̇si̇ni̇n Meta Anali̇z Yöntemi̇yle Araştirilmasi

Abstract: ÖZBu çalışmanın amacı, cinsiyetin tekno-pedagojik alan bilgisi üzerindeki etkisini meta analiz yöntemiyle incelemektir. Meta-analiz, benzer konularda yapılmış birbirinden bağımsız ve çok sayıda çalışmadan elde edilmiş sayısal verileri istatistiksel olarak analiz etme ve bu çalışmaların sonuçları hakkında genel bir yargıya varma yöntemidir. Hangi araştırmaların meta-analize dâhil edileceğine yönelik seçimlerin yapılmasında belirli ölçütler kullanılmıştır. Bu ölçütlere dayalı olarak 6 adet tez çalışmasının meta-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
0
6
0
1
Order By: Relevance
“…These results show that the total score of male on TPACK scale is higher than that of female. Although there is no meta-analysis study in the international literature to compare with this finding, it was revealed in the meta-analysis study conducted by Tuncer and Dikmen (2018) in Turkish literature that gender is not a dominant independent variable in terms of TPACK competencies. Similarly, in the study by Unlu, Kaskaya, and Coskun (2017), which is one of the primary studies on technological pedagogical content knowledge by gender, no significant difference was found by gender variable when technology pedagogy and content knowledge dimensions of social studies teacher candidates were examined.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…These results show that the total score of male on TPACK scale is higher than that of female. Although there is no meta-analysis study in the international literature to compare with this finding, it was revealed in the meta-analysis study conducted by Tuncer and Dikmen (2018) in Turkish literature that gender is not a dominant independent variable in terms of TPACK competencies. Similarly, in the study by Unlu, Kaskaya, and Coskun (2017), which is one of the primary studies on technological pedagogical content knowledge by gender, no significant difference was found by gender variable when technology pedagogy and content knowledge dimensions of social studies teacher candidates were examined.…”
Section: Discussionmentioning
confidence: 87%
“…In the Turkish literature, there is a meta-analysis study on this issue conducted by Tuncer and Dikmen (2018). In this meta-analysis study conducted with 6 master thesis studies, it was found that gender was not a dominant independent variable in terms of TPACK competencies.…”
Section: Tpack and Gendermentioning
confidence: 98%
See 1 more Smart Citation
“…In the TPACK self-confidence dimension, Bağrıyanık (2015) and Altunoğlu (2018) were in favor of male teachers; Akyıldız and Altun (2018) found a significant difference in favor of women. These different results show that gender is not a dominant independent variable in terms of TPACK dimensions (Tuncer & Dikmen, 2018).…”
Section: Discussionmentioning
confidence: 70%
“…Education, technology and social transformation can cause different gender groups to exhibit different behaviors. This situation requires reviewing study findings according to their sample group (Tuncer & Dikmen, 2016). Opinions and values about gender can differ across societies and time.…”
Section: Conclusion and Discussionmentioning
confidence: 99%